(untitled) (Research, Society and Development, 2022)
Coffin edifices buildings that commonly use resistant masonry as structural, without being based on recognized standards. This style of building began to be widespread in the 1970s in the Metropolitan Region of Recife due to the reduction of time and cost. From the 1990s, accidents in coffin buildings began to occur, along with a series of notifications of building defects. In order to map and carry out interdictions, in the necessary cases, several building inspection reports were carried out, either by determination of the Public Power or by initiative of the owners themselves. Five of these reports were selected for the present research, whose objective is to study the main defects of coffin buildings in three elements: foundation, superstructure and façade. To this end, the GUT Matrix was applied to determine the severity and resolution priority of the observed problems. After the analyses, it was shown that the damages present in the foundation and in the superstructure have priority in the resolution.